Inconsistent Justice - Saahil Gill (Canadian Journal for the Academic Mind)
This paper critically examines landmark precedents set by the International Criminal Tribunals for Rwanda (ICTR) and the former Yugoslavia (ICTY) in prosecuting sexual violence as a means of genocide. Under statutory international humanitarian law, sexual violence is not explicitly listed as a means of genocide, leaving the chambers of these aforementioned tribunals to interpret various legal instruments in order to prosecute the perpetrators of sexual violence during the armed conflicts. In this context, the ICTR set a groundbreaking precedent in the Akayesu case by recognizing sexual violence as a means of committing genocide, thereby elevating the status of these sexual crimes to one of the gravest violations under international law. By contrast, the ICTY was notably reluctant to rule sexual violence and rape as a charge of genocide, electing instead to prosecute it solely as a crime against humanity. By analyzing key cases such as Akayesu at the ICTR and Kunarac et al. and Kristic at the ICTY, this paper argues that the latter’s reluctance to recognize sexual violence as a genocidal act has influenced the International Criminal Court’s (ICC) limited application of genocide charges in contemporary cases involving sexual violence. Consequently, victims of gender-based violence during armed conflict continue to face challenges in securing proper justice and accountability. As such, this analysis highlights the need for a re-evaluation of both the existing statutory and judicial understanding of genocide under international law to reflect the ICTR’s broader recognition of the relationship between gender-based sexual violence, armed conflict, and genocidal intent.